Trends in effectiveness of inactivated influenza vaccine in children by age groups in seven seasons immediately before the COVID-19 era. Issue 22 (11th May 2022) - Shinjoh, Masayoshi; Furuichi, Munehiro; Kobayashi, Hisato; Yamaguchi, Yoshio; Maeda, Naonori; Yaginuma, Mizuki; Kobayashi, Ken; Nogayama, Taisuke; Chiga, Michiko; Oshima, Mio; Kuramochi, Yuu; Yamada, Go; et al.
Highlights: Flu vaccine effectiveness for children was analyzed for 2013/14 to 2019/20. Recent inactivated flu vaccine is effective in children and infants for flu A. Vaccine effectiveness was highest among 1 to 2 year olds for flu A and flu B. Flu vaccine effectively prevents flu A hospital admission in children aged 1–12. Abstract: Background: We have reported the vaccine effectiveness of inactivated influenza vaccine in children aged 6 months to 15 years between the 2013/14 and 2018/19 seasons. Younger (6–11 months) and older (6–15 years old) children tended to have lower vaccine effectiveness. The purpose of this study is to investigate whether the recent vaccine can be recommended to all age groups. Methods: The overall adjusted vaccine effectiveness was assessed from the 2013/14 until the 2020/21 season using a test-negative case-control design based on rapid influenza diagnostic test results. Vaccine effectiveness was calculated by influenza type and by age group (6–11 months, 1–2, 3–5, 6–12, and 13–15 years old) with adjustments including influenza seasons. Results: A total of 29, 400 children (9347, 4435, and 15, 618 for influenza A and B, and test-negatives, respectively) were enrolled. The overall vaccine effectiveness against influenza A, A(H1N1)pdm09, and B was significant (44% [95% confidence interval (CI), 41–47], 63% [95 %CI, 51–72], and 37% [95 %CI, 32–42], respectively). The vaccine was significantly effective against influenza A and B, except among children 6 to 11 months against influenza B. The age group with the highest vaccine effectiveness was 1 to 2 years old with both influenza A and B (60% [95 %CI, 55–65] and 52% [95 %CI, 41–61], respectively). Analysis for the 2020/21 season was not performed because no cases were reported. Conclusions: This is the first report showing influenza vaccine effectiveness by age group in children for several seasons, including immediately before the coronavirus disease (COVID-19) era. The fact that significant vaccine effectiveness was observed in nearly every age group and every season shows that the recent vaccine can still be recommended to children for the upcoming influenza seasons, during and after the COVID-19 era.